Association and Impact of Mathematics Anxiety Levels on the Quality of Students' Understanding Based on Skemp's Theory - Qothrunnada, Isni; Widjajanti, Djamilah Bondan (International journal of multicultural and multireligious understanding, 2025)
This study aimed to examine the association between math anxiety and students' comprehension quality based on Skemp's Theory and describe the impact of math anxiety level on students' comprehension quality. This survey research with a quantitative approach involved a population of grade 8 students in junior high schools in Bantul Regency. The sample size was 386 students using stratified proportional random sampling technique. Math anxiety and the quality of student understanding were measured using a questionnaire instrument and description questions tailored to the ratio and proportion material. This instrument has been declared valid and reliable. The data analysis technique is correspondence analysis using cross tabulation to see the frequency distribution in each category and chi-square test to check whether or not there is an association. The results of the study with a 5% significance level showed that (1) the chi square value was 0,36 (< 0,05) which means that there is an association between math anxiety and the quality of students' understanding; (2) the higher the level of math anxiety experienced by students, the lower their tendency to build relational understanding and vice versa, students with high math anxiety tend to develop instrumental understanding or even experience incomprehension of the material.